In vitro evaluation of sustained released matrix tablets containing ibuprofen: a model poorly water-soluble drug (Brazilian Journal of Pharmaceutical Sciences, 2016)
A matrix system was developed that releases ibuprofen (IB) over a 12-hour period and the influence of the polymer type and concentration on the release rate of the drug was evaluated. Tablets containing different concentrations of Carbopol (CP), hydroxypropyl methylcellulose (HPMC), or ethyl cellulose (EC) were prepared using direct compression and the drug content, content uniformity, hardness, friability, dissolution performance, and in vitro release kinetics were examined. Formulated tablets were found to be within acceptable limits for physical and chemical parameters. The release kinetics of the Carbopol(r)971P 8% formulation showed the best linearity (r 2 =0.977) in fitting zero-order kinetics, suggesting the release rate was time independent. The drug release from tablets containing 8% CP was extended over approximately 18 hours and the release kinetics were nearly linear, suggesting that this system has the potential to maintain constant plasma drug concentrations over 12 hours, which could reduce the frequency of administration and the occurrence of adverse effects associated with repeated administration of conventional IB tablets.